Exploring mental health in veterinary students: common stressors and effective coping strategies: a narrative review - Islam, Rahib K.; Cobb, Emily K.; McCowan, Hannah K.; Watson, Kylie; Bhattacharya, Kaustuv; Chandra, Anjali; Mohiuddin, Warda; Gruszynski, Karen; Wilkerson, Amanda H.; Dascanio, John J.; Davis, Robert E.; Nahar, Vinayak K. (Frontiers in Veterinary Science, 2025)
IntroductionVeterinary students face significant challenges impacting their mental health and wellbeing. The rigorous academic curriculum, high expectations, and demanding clinical training create an environment of intense pressure and constant stress. This review explores the demographic and psychosocial variables influencing mental health outcomes, highlighting common stressors and coping strategies.MethodsA systematic literature search was conducted using PubMed, CAB Abstracts, and Google Scholar. Studies published up to 2021 involving veterinary students were included. Twenty-one peer-reviewed studies met the inclusion criteria. Demographic data, stressors, mental health measures, and coping strategies were extracted and analyzed. Studies focused on various mental health aspects, including stress, anxiety, depression, and coping mechanisms. The final selection was based on relevance, quality, and comprehensiveness.ResultsThe reviewed studies indicated that rigorous academic demands, high expectations, and clinical training contribute to elevated stress levels among veterinary students. Women reported higher levels of stress, anxiety, and depression compared to men, necessitating gender-specific interventions. Social support and relationship quality were crucial for mental wellbeing, with students in supportive environments experiencing lower stress. Effective coping strategies included exercise and social activities; whereas, harmful behaviors like substance misuse exacerbated mental health issues. Despite using mental health services, barriers such as stigma and lack of awareness hindered access for some students.ConclusionThe findings underscore the need for targeted support systems to enhance the mental health and resilience of veterinary students. Interventions to promote healthy coping mechanisms, reduce stigma, and improve access to mental health resources are essential. Veterinary schools should prioritize creating a supportive environment to ensure students can manage the demands of their profession while maintaining their mental health and wellbeing.